An Economic Analysis of Thailand's Cephalopod Export Market - Sungsitthisawad, Ratana (1986)
This study attempts to provide information and evaluation of factors affecting the Thai export market of cephalopod to Japan. This was accomplished by estimating simultaneous export demand and supply equations using quarterly data from 1975 through 1983. The commodities are grouped into two, i.e. cephalopod salted in brine dried and cephalopod fresh, chilled and frozen. Export supply is explained by weighted average export price of cephalopod, lagged export quantity of cephalopod, and dummy variables while export demand is hypothesized to be a function of cephalopod weighted average export price, lagged weighted average export price, price of substitute good, Japanese's real income and dummy variables. A log linear form was selected as the function to be estimated. The estimation procedure is three stage least squares.The results for salted cephalopod indicate that supply and demand for export is price elastic while demand is income elastic. In the case of fresh cephalopod both export demand and supply are price inelastic while demand is also income elastic. Cross price elasticities of demand as compensated to substitution products (shrimps, prawns and lobsters) are found to be highly inelastic. The results also indicate that Japanese's real income has the strongest effect on both salted and fresh cephalopod demand. The seasonal effect is found to be insignificant.